Network-on-chip the next generation of system-on-chip integration - Kundu, Santanu; Chattopadhyay, Santanu (CRC Press Taylor & Francis Group, 2015)
This book provides a basic overview of topics associated with NoC-based design: communication infrastructure design, communication methodology, evaluation framework, and mapping of applications onto NoC. It details the design and evaluation of different proposed NoC structures, low-power techniques, signal integrity and reliability issues, application mapping, testing, and future trends